2021
DOI: 10.1021/acsami.1c12589
|View full text |Cite
|
Sign up to set email alerts
|

High-Safety and Dendrite-Free Lithium Metal Batteries Enabled by Building a Stable Interface in a Nonflammable Medium-Concentration Phosphate Electrolyte

Abstract: Lithium metal anodes are promising for their high energy density and low working potential. However, high reactivity and dendrite growth of lithium metal lead to serious safety issues. Lithium dendrite may form "dead lithium" or pierce the separator, which will cause low efficiency and short-circuit inside the battery. A nonflammable phosphate-based electrolyte can effectively solve the flammability problem. Also, it shows poor compatibility with lithium metal anodes, resulting in an unstable solid electrolyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…42 As the XPS results of C 1s show in Figure 4d-f 43 Notably, the intensity and content of all the peaks in EC/DEC were much higher than that in SN/DEC electrolytes, which might be attributed to the catastrophic decomposition of the electrolyte due to the catalysis of Ni 2+ /Ni 3+ . 44,45 A similar phenomenon can also been observed in the O 1s spectrum. The intensity of the O− C�O peak at 531.4 eV corresponding to the generation of LiOR, LiCO 2 OR, and Li 2 CO is significantly higher, suggesting the formation of more O-containing species, 46 as shown in Figure 4g-i 4g originated from the side reactions between diffused TM ions, and the electrolyte on the anode/ electrode interface was much stronger than that in Figure 4h-i, supposing the stable passivation layer on the cathode surface has been constructed in hybrid electrolytes, thus preventing the dissolution of TM ions.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…42 As the XPS results of C 1s show in Figure 4d-f 43 Notably, the intensity and content of all the peaks in EC/DEC were much higher than that in SN/DEC electrolytes, which might be attributed to the catastrophic decomposition of the electrolyte due to the catalysis of Ni 2+ /Ni 3+ . 44,45 A similar phenomenon can also been observed in the O 1s spectrum. The intensity of the O− C�O peak at 531.4 eV corresponding to the generation of LiOR, LiCO 2 OR, and Li 2 CO is significantly higher, suggesting the formation of more O-containing species, 46 as shown in Figure 4g-i 4g originated from the side reactions between diffused TM ions, and the electrolyte on the anode/ electrode interface was much stronger than that in Figure 4h-i, supposing the stable passivation layer on the cathode surface has been constructed in hybrid electrolytes, thus preventing the dissolution of TM ions.…”
Section: Resultssupporting
confidence: 75%
“…As the XPS results of C 1s show in Figure d-f, the characteristic peaks located at 284.7, 285.7, 286.5, and 288.3–288.5 eV were assigned to C–C/C–H, C–O, CO, and O–CO, respectively . Notably, the intensity and content of all the peaks in EC/DEC were much higher than that in SN/DEC electrolytes, which might be attributed to the catastrophic decomposition of the electrolyte due to the catalysis of Ni 2+ /Ni 3+ . , A similar phenomenon can also been observed in the O 1s spectrum. The intensity of the O–CO peak at 531.4 eV corresponding to the generation of LiOR, LiCO 2 OR, and Li 2 CO is significantly higher, suggesting the formation of more O-containing species, as shown in Figure g-i.…”
Section: Resultsmentioning
confidence: 88%
“…Indeed, Zhang et al showed that adjusting the lithium salt concentration and introducing FEC as an additive in the electrolyte allow the formation of a stable solid electrolyte interphase (SEI) that favors a nondendritic lithium deposition over cycling. [ 13 ] The increase of salt concentration in the electrolyte tends to modify its properties as well as battery performance. For example, the flammability of carbonate liquid electrolytes has shown to be reduced just by increasing the lithium salt concentration from 1 to 4 M. [ 14 ] This effect can be attributed, in highly concentrated electrolytes, to the low amount of free solvent molecules, usually responsible of the electrolyte flammability, because many of them are engaged in Li + solvation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Zhang et al showed that adjusting the lithium salt concentration and introducing FEC as an additive in the electrolyte allow the formation of a stable solid electrolyte interphase (SEI) that favors a nondendritic lithium deposition over cycling. [13] The increase of salt concentration in the electrolyte tends to modify its properties as well as battery performance. DOI: 10.1002/ente.202201037…”
Section: Introductionmentioning
confidence: 99%
“…Thermal stability issues, such as re and explosion through thermal runaway, are fundamentally caused by the use of volatile and ammable liquid electrolytes with linear or cyclic organocarbonate compounds. [1][2][3][4] Thermal runaway can be initiated by overcharging, external shock/cell defects, or excessive heat generation, which destabilizes the organic liquid electrolytes, resulting in overheating, heat accumulation, combustion, and eventual battery explosion. 5 Although a wide range of ame-retarding additives have been developed to avoid combustion and explosion, they involve a trade-off between ammability and electrochemical cell performance.…”
Section: Introductionmentioning
confidence: 99%